COMPARATIVE REVIEW OF THE EFFECTIVENESS OF DIFFERENT SURGICAL TECHNIQUES IN THE MANAGEMENT OF GINGIVAL RECESSION - Mijatović, Jelena; Jovičić, Bojan; Urošević, Zoran; Okičić, Nemanja; Milovanović, Boban; Tričković, Vesna; Smiljanić, Marko; Tesla, Zlata (Sanamed, 2024)
Mucogingival anomalies arise from anatomical and morphological irregularities within the mucogingival complex of periodontal tissues, representing deviations from the normal dimensions and morphology of the gingiva-alveolar mucosa relationship. According to the American Academy of Periodontology glossary, gingival recessions are defined as the exposure of the tooth root surface caused by the apical displacement of the gingiva relative to the cemento-enamel junction. In addition to aesthetic concerns, gingival recessions lead to increased sensitivity and ineffective plaque control, which can ultimately result in tooth loss. To address these issues, procedures are performed to cover exposed roots and restore the normal function and appearance of the mucogingival complex. The treatment for gingival recessions is primarily surgical, aiming for complete root coverage with long-term stability. Various methods are available, but the gold standard involves using a connective tissue graft in combination with a coronally advanced flap. This paper compares three treatment methods: the coronally advanced flap (CAF), CAF combined with a connective tissue graft, and CAF with porcine collagen matrix application. The primary objective is to identify which surgical method yields the best clinical outcomes. Nine studies involving 303 patients demonstrated that the highest root coverage is achieved with CAF combined with a connective tissue graft, showing a reduction in recession depth of 2.64 mm, an increase in the keratinized gingival zone of 1.05 mm, and a reduction in pocket depth of 0.36 mm. CAF combined with porcine collagen matrix provided slightly lower results, while CAF alone yielded the lowest outcomes.